Crimes and punishment in new perspective - Agarwal, Rajendra Saran; Sarvesh Kumar; International Association of Penal Law. (Delhi, India : Mittal Publications : Distributed by Mittal Publishers' Distributors, 1986)
Papers presented at a meeting organized by International Association of Penal Law, New Delhi, 1982.
Spine title: Crimes & punishment in new perspective.
Includes bibliographies and index.
Keywords: Capital punishment -- India -- Congresses; Rape -- India -- Congresses; Capital punishment -- Congresses; Diplomatic privileges and immunities -- India -- Congresses; Rape -- Congresses